Compulsão alimentar na adolescência: uma abordagem junguiana - um estudo sobre a dinâmica psíquica através do método de Rorschach - Bárbara, Raquel de Queiroz (2011)
Obesity and eating difficulties can be considered, in current times, as a pandemic. There's a subgroup of individuals who have inadequate eating patterns and therefore, suffer from eating disorders. In this category, there are those who suffer from Binge Eating Disorder. The first symptoms usually appear during childhood o adolescence. This research investigates the psychic dynamics of teenagers who have Binge Eating symptoms by using the Rorschach Method. Seven participants who felt loss of control eating and had episodes of Binge Eating were selected based on the Questionnaire on Eating and Weight Patterns - Revised. These teenagers were interviewed and submitted to the Rorschach test. The analysis of the material collected based on these implements made it clear that there was a behavioral pattern. These adolescents have difficulties to confront their inner self and to deal with affection. Moreover, they have problems in socializing. The qualitative analysis of the answers given by the participants when exposed to the Rorschach figures have granted us a greater comprehension of the psychic dynamics involved when these symptoms are shown. A balking family environment - which fails to contribute to the building of a rich inner self -, and a negative maternal and/or paternal complexes are determinant to this condition. These adolescents are unable to acquire the necessary psychic conditions to face an intense period of change, such as the one which defines the turbulent teenage years. Thus, they strive to build an adequate persona capable of relating to the external world and the construction of a more integrated ego. These teenagers go through an empty period: they are incapable of going back on their development and remain in a safer environment, inside the Family scenery but also face a series of obstacles which are hari to overcome so that they car evolve. In this context, compulsive crisis is part of the equilibrium they manage to reach. By eating, they find the only confort and relief for their failures, for what the~ are unable to express and feel impotent to deal